Unconventional multiple ring structure formation from evaporation-induced self-assembly of polymers - Bi, Wuguo (2013)
The formation of multiring deposits of poly(2-vinylpyridine) (P2VP) from the evaporation of a P2VP-(2,6-lutidine + water) drop on a glass substrate does not conform to the conventional pinning–depinning mechanism. Instead, ringlike deposits are formed when the droplet undergoes several cycles of spreading and receding where, for each spreading event, a P2VP ridge is formed at the contact line when the polymer flows toward the outward advancing edge. The complex interplay between an outward solutal-Marangoni flow due to a higher concentration of the polymer at the contact line and an inward solvent-Marangoni flow arising from the differences in volatilities and surface tensions of the pure solvent components plays an important role in enhancing the droplet spreading rate. The newly discovered surface patterning mechanism has important implications in the development of novel techniques for inducing self-assembly of functional materials from evaporating drops.